Análise da percepção de estresse e recuperação e de variáveis fisiológicas em diferentes períodos de treinamento de nadadores de alto nível - Rauno Alvaro de Paula Simola (2008)
This study had the aim to investigate the stress recovery state, through RESTQSportquestionnaire, the salivary cortisol concentration and the plasmatic creatinekinase activity (CK) during the rest, in 3 different moments of a training season (T1,T2 and T3), over 2 months, when the athletes were submitted to different loadtraining levels. Moreover, to investigate a possible relationship between thepsychological variables with the physiological ones in T1, T2 and T3. 13 male hightrained swimmers (17,7 + 1,3 years old) participated in this study. During T1, theathletes were submitted to considerate moderate load training during one week.During T2, they were submitted to the same volume and to a heavier load intensitytraining during one week, when compared to T1. In the week T3, the load trainingwere reduced substancially in terms of volume and intensity. Few days after T3, theswimmers participated in an important contest during the whole season. There wereno differences in recovery stress state between T1 and T2. The recovery stress stateimproved from T2 to T3 and from T1 to T3 as well. Besides, there were significantlyaugments in salivary cortisol between T1 and T2 (0,23 ìg/dL + 0,15; 0,38 ìg/dL +0,15), between T2 and T3 (0,38 ìg/dL + 0,15 + 0,47 + 0,19 ìg/dL) and between T1 eT3 (0,23 ìg/dL + 0,15; 0,47 + 0,19 ìg/dL). The CK activity reduced significantly fromT1 to T3 (289,18 + 112,86 U/L; 167,92 + 57,14 U/L). These results indicate thatdifferent variables utilized during the sport training monitoring show differentsensitivity to changes in load training, therefore, the sport training monitoring in highlevel swimmers should be done in a multidisciplinary manner.